Emergency Governance in Liberal Democracies - Leonov, Max (My University, 2017)
This dissertation explores conceptual, normative, and institutional dimensions of the emergency problematic and defends judicial participation in emergency governance. I develop my arguments on the basis of Posner and Vermeule’s discussion in their book Terror in the Balance. I reject their institutional account of emergency governance captured in their deference thesis by showing its incompatibility with fundamental liberal democratic commitments. As I argue, Posner and Vermeule’s call for across-the-board judicial deference to the executive during emergencies is unwarranted in a number of cases, most notably those involving conflicts of constitutional rights. I also reject Posner and Vermeule’s account of emergency policymaking captured in their tradeoff thesis by showing that it does not provide a suitable criterion by means of which the legitimacy of emergency policies could be determined. My arguments against the tradeoff and deference theses are based in part on my critique of Posner and Vermeule’s conception of emergency situations. In fleshing out my conception of emergency, I present and defend a methodological approach to studying the emergency problematic and offer an extensive discussion of exceptionality associated with emergencies. My conclusion is that it is necessary to take in account liberal democratic commitments in the process of emergency policymaking and that judicial review of the executive during periods of emergency is conducive to legitimate emergency governance.
Keywords: emergency, constitutional law, judicial deference